Transcriptome profiling shows gene regulation patterns in a flavonoid pathway in response to exogenous phenylalanine in Boesenbergia rotunda cell culture - Md-Mustafa, N.D.; Khalid, N.; Gao, H.; Peng, Z.; Alimin, M.F.; Bujang, N.; Ming, W.S.; Mohd-Yusuf, Y.; Harikrishna, J.A.; Othman, R.Y. (BioMed Central, 2014)
Background Panduratin A extracted from Boesenbergia rotunda is a flavonoid reported to possess a range of medicinal indications which include anti-dengue, anti-HIV, anti-cancer, antioxidant and anti-inflammatory properties. Boesenbergia rotunda is a plant from the Zingiberaceae family commonly used as a food ingredient and traditional medicine in Southeast Asia and China. Reports on the health benefits of secondary metabolites extracted from Boesenbergia rotunda over the last few years has resulted in rising demands for panduratin A. However large scale extraction has been hindered by the naturally low abundance of the compound and limited knowledge of its biosynthetic pathway.